Prevalence of occupational injuries among construction workers in Karachi, Pakistan. - Asad Allana; Aamir Ali Khan; Muhammad Yousuf; Paul Cullinan; Asaad Ahmed Nafees (PLOS Global Public Health)
The construction industry in Pakistan employs 8% of the labour force, contributing 3% to the national GDP. This study aimed to determine the prevalence and associated factors of occupational injuries among construction workers in Karachi. We conducted a cross-sectional survey among 448 men from 10 construction sites in Karachi between June and October 2022. Workers aged ≥18 years involved in masonry, cleaning, machine operating, and supervision tasks were recruited and completed a structured, interviewer-administered questionnaire. Occupational injury was defined as "any injury at work over the last year for which the worker sought medical care or took time off work". We found the prevalence of occupational injury to be 26% (n = 116). Workers from small construction were more likely to report injuries, with an OR of 2.01 (95% CI: 1.30-3.12). Additionally, those working more than 8 hours daily had greater odds of injury, with an OR of 2.30 (95% CI: 1.45-3.67). This study found a high prevalence of injuries among construction workers in Karachi, Pakistan, emphasizing the need for preventive measures and interventions for improving health and safety at construction sites.